ANALISIS MANAJEMEN PERSEDIAAN USAHA KONVEKSI DALAM MENINGKATKAN PENDAPATAN MENURUT PERSPEKTIF BISNIS SYARIAH - Nurvira Annisa; Zulhelmi Zulhelmi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This research is motivated by the importance of effective inventory management in hijab manufacturing businesses to address fluctuations in market demand and minimize operational costs. The research problem is how inventory management in the hijab manufacturing sector can increase revenue from the perspective of Islamic business principles. The objective of this study is to analyze inventory management at Leni Hijab and its impact on revenue enhancement, with a focus on the application of Islamic business principles. The research employs a descriptive qualitative approach, using data collection techniques such as interviews with the business owner and direct field observations. The data obtained are analyzed to provide a real picture of the inventory management practices implemented. The results indicate that effective inventory management can increase revenue by following systematic stages, such as planning, raw material management, receiving, storage, and inventory control. This allows business owners to minimize the risk of losses due to excess or insufficient stock. Additionally, the selection of quality raw materials, improved customer service, and optimization of product availability play crucial roles in maintaining product quality. The application of Islamic business principles, aligned with the teachings of Allah SWT in Qs. Al-Mutaffifin verses 1-3, serves as a fundamental basis for this process. By ensuring quality at every stage of production, Leni Hijab is able to maintain customer satisfaction and build sustainable consumer loyalty